Examining factors associated with heavy episodic drinking among college undergraduates - Kristen Scholly; Alan R. Katz; Lisa Kehl (Health Psychology Research, 2014)
Heavy episodic drinking among college students is a serious health concern. The purpose of this study was to identify factors associated with heavy episodic drinking behaviors amongst a predominately Asian undergraduate college student population in the United States. A survey measuring alcohol use behaviors was completed by a random sample of 18-24 year old undergraduates during April, 2011. A multivariate logistic regression analysis was conducted to determine factors associated with students’ heavy episodic drinking behavior. Independent factors associated with heavy episodic drinking included living on campus, ethnicity, perceived drinking behavior among peers, and a belief that alcohol is a central part of one’s social life. Heavy episodic drinking was also associated with poor academic performance. Campus-wide educational strategies to reduce heavy episodic drinking among college undergraduates should incorporate accurate information regarding alcohol use norms to correct students’ perceived over estimation of their peers alcohol consumption rates and the under estimation of students protective alcohol use behaviors. These efforts should focus in on-campus residence halls where a higher occurrence of heavy episodic drinking is often found.